ANALISIS IMPLEMENTASI PEMBELAJARAN ONLINE PADA MATA PELAJARAN MATEMATIKA JENJANG SEKOLAH DASAR - Sabina Ndiung; Trifonia Atin Statianin; Virgorius Jehadin; Alfonsus Sandrio Norman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article describes the teacher's perception of the mathematical learning subject implementation by using the online mode in elementary schools. The research was a quantitative descriptive study by involving ten elementary school teachers as the sample. The research was conducted at ten elementary schools in Macang Pacar, West Manggarai. The data collection technique used a questionnaire, which consisted of 25 questions related to the implementation of online learning in the midst of the Covid-19 pandemic and was tested first to test the validity and reliability of the instrument. Based on the results of the instrument validity test, it was found that the teachers' perception instruments were valid with a reliability coefficient of 0.84 in the high category. The data analysis technique used quantitative-descriptive analysis. The results showed that based on the results of the analysis by respondents on 25 items of questionnaire instruments with three dimensions, they are dimensions of teaching materials with the average of 2.84, the dimensions of students’ interaction with an average of 4.14, and the dimensions of the learning environment with the average of 2.92. Based on the results, it can be concluded that the implementation of online mathematical learning subjects for students in the Macang Pacar West Manggarai was not implemented well. Based on the findings, it is recommended for teachers to apply online learning by considering supporting facilities and infrastructure that could facilitate interactive learning activities by considering the justice principle for the students.